PENGARUH PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN PADA SISWA KELAS VII SMPN 1 KECAMATAN GUGUAK - Sri Mures Walef; Rita Arianti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This study aims to find out (1) empirical data on the influence of jigsaw type cooperative learning on the reading comprehension skills of grade VII students of SMP N I Kecamatan Guguak, and (2) to know empirical data of conventional learning influence on reading comprehension skills of grade VII students of SMP N I Kecamatan Guguak.. Data analysis shows that, jigsaw type cooperative learning is influential in comprehension reading skills. This is evidenced by the increase in student value, the mean time of the mean value is 57.76. After applying jigsaw type cooperative learning in the learning process in this class, obtained the improvement of student learning outcomes with the average value 78.06. While conventional learning is also influential, although the increase in value is not too high. The preetest time average value is 63.33. After applying conventional learning, there is an increase of student learning outcomes with average score 71,05. Thus, the learning outcomes of experimental class students taught by jigsaw type cooperative learning are better than the students' control class learning outcomes taught by conventional learning. Keywords: Jigsaw Cooperative Learning, Understanding Reading Skills.